Lo Stakeholder Engagement e il Global Report di Boxmarche Spa - Del Baldo, Mara (Piccola Impresa / Small Business, 2013)
The aim of this paper is to suggest a case study pertaining to an Italian firm that represents a paradigmatic example of social engagement and the capacity to successfully pursue socio-economic and environmental development. Although Boxmarche Spa belongs to the SME category, the goals it has reached made it an example of “best practices” in the framework of corporate social responsibility management. Over the years the firms has obtained many important awards for excellence in this field. The case offers some distinctive elements as regards the following aspects: the process of Corporate Social Responsibility (through a description of the entrepreneurial value and the CSR actions) as well as of the high-quality process of communication of the firm’s social commitment. In this context, the Global Report represents a driving factor in the enlargement and enforcement of the process of stakeholder relationships that Boxmarche has been implementing.